A Systematic Review of Patient‐Reported Outcomes in Primary Biliary Cholangitis and Primary Sclerosing Cholangitis. Issue 10 (1st August 2020) - Kim, Hannah P.; Lieber, Sarah R.; Rogers, Michael E.; Moon, Andrew M.; Loiselle, Marci; Walker, Jennifer; Assis, David N.; Safer, Ricky; Gomel, Rachel; Evon, Donna M.
Abstract : Primary biliary cholangitis (PBC) and primary sclerosing cholangitis (PSC) are associated with decreased health‐related quality of life and debilitating symptoms. These experiences can be defined as patient‐reported outcome (PRO) concepts and measured using PRO instruments. We identified all PRO concepts and instruments used in the PBC and PSC literature. This systematic review identified PBC and/or PSC studies from January 1, 1990, to May 6, 2019, that measured at least one PRO concept. Study population, design, PRO concept, PRO instrument, and validation data for PRO instruments were investigated. We provided descriptive statistics of PRO concepts and instruments used, stratified by population type. Use of PRO concepts and instruments were assessed over time. The search yielded 318 articles (69% in PBC, 18% in PSC, 13% in both, and 24% in drug trials). Forty‐nine unique PRO concepts were identified. The five most common PRO concepts included pruritus (25%), fatigue (19%), broad health‐related quality of life (16%), gastrointestinal adverse events (6%), and physical adverse events (6%). Only 60% of PRO concepts were measured with a PRO instrument, most of which were nonvalidated visual analogue or numeric rating scales. Only three of 83 PRO instruments were developed with feedback from the target populations (one for PBC, one for PSC, and one for both), and only six documented any psychometric testing in the target populations. Use of PRO instruments increased over time from 30% in the 1990s to 67% by 2019. Conclusion: The overwhelming majority of PRO instruments used in PBC/PSC were nonspecific and lacked patient validation or empirical justification. Significant opportunities exist to use qualitative methods to better understand patient experiences, and translate this knowledge into meaningful, patient‐driven study outcomes.